High-wear-resistance preservation box cover and preparation method thereof
By introducing modified nanofillers and self-repair microcapsules with loaded dynamic covalent bond precursors into the polypropylene fresh-keeping box lid, the problem of insufficient wear resistance and inability to self-repair is solved, and the high material is achieved Wear resistance and self-repair ability extend service life.
Patent Information
- Application Number
- CN202411554825.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polypropylene fresh-keeping lids are not wear-resistant during long-term use, prone to scratches and wear, and cannot repair themselves, resulting in reduced sealing and poor food fresh-keeping effect.
Modified nanofillers are introduced into polypropylene, and nanofillers loaded with dynamic covalent bond precursors are realized through Diels-Alder reaction, and combined with self-healing microcapsules, the material's wear resistance and self-healing ability.
It significantly improves the wear resistance and self-repairing ability of the polypropylene fresh-keeping lid, extends the service life, reduces material replacement due to wear, and maintains the mechanical strength and wear resistance of the material.
Smart Images

Figure BDA0005116119170000111 
Figure BDA0005116119170000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food packaging materials, and in particular to a highly wear-resistant fresh-keeping box cover and a preparation method thereof. Background Art
[0002] With the improvement of people's quality of life and the enhancement of environmental awareness, the safety, durability and reusability of food packaging materials have become the focus of attention of consumers and manufacturers. Especially in daily necessities such as fresh-keeping boxes, the wear resistance and long-term use performance of fresh-keeping box covers are particularly important. Traditional plastic fresh-keeping box covers are mostly made of thermoplastic plastics such as polypropylene (PP). This type of material is widely used in food packaging due to its advantages such as light weight, non-toxicity and chemical corrosion resistance. However, existing fresh-keeping box covers often face some technical challenges during long-term use, especially in terms of wear resistance and damage repair.
[0003] Polypropylene is the mainstream choice of food packaging materials. Although it has good chemical resistance and low density, its wear resistance is weak. In particular, the fresh-keeping box cover is prone to scratches and wear when it is repeatedly opened and closed, washed (including dishwasher washing) and in contact with other hard objects. This not only affects the appearance of the product, but may also cause the sealing of the cover to decrease, thereby affecting the preservation effect of food.
[0004] In addition, the existing polypropylene fresh-keeping box lid cannot self-repair after suffering mechanical damage (such as cracks and scratches), and the lid needs to be replaced. This not only increases the cost for users, but also does not meet the requirements of modern society for environmental protection and sustainable development. Therefore, the development of a fresh-keeping box lid material with high wear resistance and self-repair ability has become an urgent problem to be solved in the industry. Summary of the invention
[0005] In view of this, the present invention proposes a highly wear-resistant fresh-keeping box cover and a preparation method thereof, aiming to improve the wear resistance of the polypropylene fresh-keeping box cover.
[0006] The technical solution of the present invention is implemented as follows: the present invention provides a highly wear-resistant fresh-keeping box cover, the raw materials of which include: polypropylene and modified nanofiller, wherein the modified nanofiller is a nanofiller loaded with a dynamic covalent bond precursor, and the mass ratio of polypropylene: modified nanofiller is 1: (0.01-0.05).
[0007] Introducing modified nanofillers into the polypropylene (PP) matrix, especially nanofillers loaded with dynamic covalent bond precursors, can disperse in the polypropylene matrix and improve the wear resistance of the material. Dynamic covalent bond precursors give the material self-healing capabilities through reversible chemical reactions, and can restore the structure by rearranging the molecular chains when the material is slightly damaged. The modified nanofillers not only improve the mechanical properties of the material, especially the wear resistance, but also further extend the service life of the fresh-keeping box cover through the self-healing properties of dynamic covalent bonds, reducing the material replacement caused by wear.
[0008] In some embodiments, the dynamic covalent bond precursors are fumaric anhydride and cyclopentadiene.
[0009] Fumaric anhydride and cyclopentadiene are classic Diels-Alder reaction precursors. The Diels-Alder reaction is reversible and can bond and break under specific conditions (such as temperature), achieving self-repair of the material. When the material is damaged, heating can cause the Diels-Alder reaction to proceed in reverse, regenerating dienes and diene precursors and restoring the material's properties. Through this dynamic covalent bond precursor, the material can achieve automatic repair when slightly damaged, extending its service life and maintaining the material's mechanical strength and wear resistance.
[0010] In some embodiments, the preparation method of the modified nanofiller includes: adding the nanofiller to ethanol to prepare a suspension with a mass concentration of 1-5wt%, adding 1-2wt% of γ-glycidyloxypropyltrimethoxysilane based on the mass of the nanofiller, ultrasonically stirring for 1-2h, then heating to 50-70°C, stirring at this temperature for 2-4h, filtering and drying to obtain an activated filler, adding the activated filler to a fumaric anhydride solution, heating to 50-60°C, stirring at this temperature for 2-3h, filtering and drying, and then adding it to a cyclopentadiene solution, heating to 30-50°C, stirring at this temperature for 1-3h, filtering and drying to obtain a modified nanofiller.
[0011] By modifying the surface of the nanofiller with a silane coupling agent (such as GPTMS), reactive groups can be introduced on the surface of the nanofiller, thereby improving the compatibility and dispersibility of the filler with the polypropylene matrix. Subsequently, fumaric anhydride and cyclopentadiene are loaded on the surface-modified nanofiller, respectively, and bonded to the filler surface by chemical adsorption or reaction to form a modified nanofiller with self-healing function. Through surface modification and loading of dynamic covalent bond precursors, the nanofiller can be evenly dispersed in the polypropylene matrix and endow the material with good self-healing properties. At the same time, the nanofiller enhances the mechanical properties and wear resistance of the material.
[0012] In some embodiments, the nanofiller is nano-silicon dioxide, and the average particle size thereof is 20-100 nm.
[0013] Nano-silica has an extremely high specific surface area and good mechanical properties, which can significantly improve the wear resistance and mechanical strength of the material. After chemical modification, its surface can also load dynamic covalent bond precursors, further giving the material self-healing function. The introduction of nano-silica improves the wear resistance and rigidity of the material, while the dynamic covalent bond precursors it loads ensure the self-healing ability of the material.
[0014] In some embodiments, the raw material also includes self-healing microcapsules, and the mass ratio of polypropylene to self-healing microcapsules is 1:(0.01-0.05). The core material of the self-healing microcapsules is at least one of dioxanone and polybutyrolactone diol, and the shell material is polyurethane.
[0015] The core of self-healing microcapsules is to encapsulate self-healing monomers in shell materials. When the material is damaged, the microcapsules rupture and release the self-healing monomers inside, which fill the cracks or damage through polymerization reactions and restore the integrity of the material. The introduction of self-healing microcapsules provides a dual repair mechanism: in the case of major damage, the self-healing monomers are released through the rupture of the microcapsules to fill the damaged area, significantly improving the service life and damage resistance of the material.
[0016] In some embodiments, the method for preparing the self-repairing microcapsule comprises:
[0017] Prepare the aqueous phase: add 0.5-1 wt% polyvinyl alcohol to deionized water, heat to 55-65°C, stir to dissolve, and cool to obtain the aqueous phase;
[0018] Preparation of oil phase: dissolving an appropriate amount of core material and isocyanate in dichloromethane to form an oil phase, wherein the mass concentration of the core material in the oil phase is 3-5wt%, and the amount of isocyanate is 1-5wt% of the core material;
[0019] Emulsification: slowly add the oil phase to the water phase, stirring and emulsifying at 3000-5000 rpm, stirring for 20-30 minutes, the volume ratio of oil phase to water phase is 1: (4-10);
[0020] Polymerization: Add polyisocyanate to the emulsified system and heat to 50-60°C. After the addition is complete, stir the mixture for 2-3 hours at this temperature, filter, wash and dry to obtain microcapsules.
[0021] The preparation method uses an in-situ polymerization method to disperse the self-repairing monomer and isocyanate in the oil phase and the water phase, and then forms a polyurethane or polyurea shell on the surface of the oil droplet through emulsification and polymerization reaction to wrap the self-repairing monomer and form a self-repairing microcapsule. The self-repairing microcapsule shell prepared by this method is dense and uniform, and can stably release the internal self-repairing monomer when the material is damaged, ensuring the self-repairing effect, and has a long storage stability.
[0022] In some embodiments, the drying temperature is 50-60°C.
[0023] The control of drying temperature is crucial to the formation and stability of the microcapsule shell. A lower drying temperature helps maintain the activity of the core material and prevents the self-healing monomer from reacting prematurely during the drying process. A drying temperature controlled at 50-60°C ensures the stability of the microcapsule shell while maintaining the self-healing activity of the core material, ensuring the storage performance and self-healing effect of the microcapsule.
[0024] In some embodiments, the core material is obtained by mixing dioxanone and polybutyrolactone diol in a mass ratio of 1:(2-3).
[0025] The mixture of PDX and PBAD can provide two different types of self-healing mechanisms: PDX repairs cracks through ring-opening polymerization, while PBAD restores the strength of the material through esterification. Adjusting the ratio of the two can optimize the repair effect and speed. Through the synergistic effect of the two self-healing monomers, the material can have both rapid repair ability and high toughness, further improving durability and repair efficiency.
[0026] The second aspect of the present invention also provides a method for preparing the above-mentioned fresh-keeping box cover, comprising the following steps:
[0027] The raw materials are mixed and added into a twin-screw extruder for melt blending and extrusion, the extruded composite material particles are cooled and collected, and then injection molded by an injection molding machine to obtain a wear-resistant fresh-keeping box cover.
[0028] After mixing the raw materials, they are melt blended through a twin-screw extruder to ensure uniform dispersion of the modified nanofiller and self-healing microcapsules in the polypropylene matrix. The melt blending process can effectively avoid filler agglomeration and ensure the uniformity of the material. This process ensures uniform dispersion of the modified nanofiller and self-healing microcapsules through melt blending, making the material perform well in wear resistance and self-healing properties.
[0029] In some embodiments, the extruder has a feeding zone temperature of 160-180°C, a melting zone temperature of 180-200°C, and a discharge zone temperature of 190-210°C.
[0030] The extrusion temperature of 160-210℃ can ensure the melting of the polypropylene matrix and the effective dispersion of the modified nanofillers and self-healing microcapsules. Different temperature controls are used in different areas to ensure processing stability and material uniformity. Through precise temperature control, the material can maintain efficient processing performance during the extrusion process, while ensuring that the nanofillers and microcapsules are not degraded or destroyed, ensuring the final performance of the material.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention endows the polypropylene fresh-keeping box cover with excellent wear resistance and self-healing ability by introducing nanofillers modified by dynamic covalent bond precursors, greatly improving the service life and mechanical properties of the material. This design is suitable for food packaging materials with high requirements for high durability and self-healing performance. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0035] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0036] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0037] Example 1
[0038] This embodiment provides a preparation scheme for a highly wear-resistant fresh-keeping box cover:
[0039] Materials preparation:
[0040] Polypropylene: 100 parts, melt flow rate (MFR) of 4 g / 10 min, commercial polypropylene;
[0041] Modified nanofiller: Nano-silica (particle size 50nm), surface modified. Its surface is treated with GPTMS and loaded with fumaric anhydride and cyclopentadiene as dynamic covalent bond precursors. The mass ratio of modified nanofiller to polypropylene is 1:0.03, and the modified nanofiller is 3 parts.
[0042] Preparation of modified nanofillers:
[0043] 50 nm nano-silicon dioxide was added into ethanol to prepare a suspension with a mass concentration of 3 wt %.
[0044] 1.5 wt% of γ-glycidyloxypropyltrimethoxysilane (GPTMS) based on the mass of the nanofiller was added, and the mixture was subjected to ultrasonic stirring for 1 hour, and then heated to 60° C., stirred for 2 hours, and filtered and dried to obtain a surface-modified nanofiller.
[0045] The activated nanofiller was added into a dichloromethane solution containing 10 wt % fumaric anhydride, heated to 55° C., stirred and reacted for 3 hours, and filtered and dried.
[0046] Then, the modified nanofiller is added into a dichloromethane solution containing 10 wt% of cyclopentadiene, heated to 40° C., stirred and reacted for 2 hours, filtered and dried to obtain a modified nanofiller loaded with a dynamic covalent bond precursor.
[0047] Preparation of fresh-keeping box lid:
[0048] 100 parts of polypropylene and 3 parts of modified nanofiller were mixed evenly and put into a twin-screw extruder for melt blending. The temperature of the feed zone of the extruder was 170°C, the temperature of the melting zone was 190°C, and the temperature of the discharge zone was 200°C. After the extruded composite material was cooled, it was cut into test samples.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the amount of the modified nano filler is 1 part, and the mass ratio of the modified nano filler to polypropylene is 1:0.01.
[0051] The temperature of the twin-screw extruder was set at 160° C. in the feed zone, 180° C. in the melt zone, and 190° C. in the discharge zone. The material was cooled and prepared into samples.
[0052] Example 3
[0053] The difference between this embodiment and embodiment 1 is that the amount of the modified nano filler is 5 parts, and the mass ratio of the modified nano filler to polypropylene is 1:0.05.
[0054] The temperature of the twin-screw extruder was set at 180° C. in the feeding zone, 200° C. in the melting zone, and 210° C. in the discharging zone. The material was cooled and prepared into samples.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that it further includes one portion of self-repairing microcapsules.
[0057] The preparation method of the self-repairing microcapsules includes:
[0058] Add 1 wt% polyvinyl alcohol to deionized water, heat to 60°C, stir to dissolve, and cool to obtain an aqueous phase;
[0059] Dissolving dioxanone and isocyanate in dichloromethane to form an oil phase, wherein the mass concentration of dioxanone in the oil phase is 4%, and the amount of isocyanate used is 3wt% of the dioxanone;
[0060] The oil phase was slowly added dropwise to the water phase, and the mixture was stirred at 4000 rpm for emulsification. The stirring process lasted for 25 minutes, and the volume ratio of the oil phase to the water phase was 1:5.
[0061] Polyisocyanate was added dropwise to the emulsified system, the amount of polyisocyanate was 1 wt% of dioxanone, and the system was heated to 5°C. After the addition was completed, the system was stirred at this temperature for 2.5 hours, filtered, washed, and dried at 55°C to obtain microcapsules.
[0062] Example 5
[0063] The difference between this embodiment and embodiment 1 is that it further includes one portion of self-repairing microcapsules.
[0064] The preparation method of the self-repairing microcapsules includes:
[0065] Add 1 wt% polyvinyl alcohol to deionized water, heat to 60°C, stir to dissolve, and cool to obtain an aqueous phase;
[0066] Dissolving polybutyrolactone diol and isocyanate in dichloromethane to form an oil phase, wherein the mass concentration of dioxanone in the oil phase is 4%, and the amount of isocyanate is 3wt% of the polybutyrolactone diol;
[0067] The oil phase was slowly added dropwise to the water phase, and the mixture was stirred at 4000 rpm for emulsification. The stirring process lasted for 25 minutes, and the volume ratio of the oil phase to the water phase was 1:5.
[0068] Polyisocyanate was added dropwise to the emulsified system, the amount of polyisocyanate was 1 wt% of polybutyrolactone diol, and heated to 5°C. After the addition was completed, the system was stirred at this temperature for 2.5 hours, filtered, washed, and dried at 55°C to obtain microcapsules.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 1 is that it further includes one portion of self-repairing microcapsules.
[0071] The preparation method of the self-repairing microcapsules includes:
[0072] Add 1 wt% polyvinyl alcohol to deionized water, heat to 60°C, stir to dissolve, and cool to obtain an aqueous phase;
[0073] Dissolve dioxanone, polybutyrolactone diol and isocyanate in dichloromethane to form an oil phase, wherein the mass ratio of dioxanone to polybutyrolactone diol is 1:2, the mass concentration of the core material in the oil phase is 4%, and the amount of isocyanate is 3wt% of the core material;
[0074] The oil phase was slowly added dropwise to the water phase, and the mixture was stirred at 4000 rpm for emulsification. The stirring process lasted for 25 minutes, and the volume ratio of the oil phase to the water phase was 1:5.
[0075] Polyisocyanate was added dropwise to the emulsified system in an amount of 1 wt% of the core material, and heated to 5°C. After the addition was completed, the system was stirred at this temperature for 2.5 hours, filtered, washed, and dried at 55°C to obtain microcapsules.
[0076] Example 7
[0077] Based on Example 6, the difference is that the mass ratio of dioxanone to polybutyrolactone diol is 1:1.
[0078] Example 8
[0079] Based on Example 6, the difference is that the mass ratio of dioxanone to polybutyrolactone diol is 1:3.
[0080] Example 9
[0081] Based on Example 6, the difference is that the mass ratio of dioxanone to polybutyrolactone diol is 1:4.
[0082] Example 10
[0083] The method is based on Example 4, except that the added amount of microcapsules is 0.5 parts.
[0084] Embodiment 11
[0085] The method is based on Example 4, except that the amount of microcapsules added is 2 parts.
[0086] Example 12
[0087] The method is based on Example 4, except that the amount of microcapsules added is 3 parts.
[0088] Comparative Example 1
[0089] Based on Example 1, the only difference is that the modified nano-silicon dioxide is replaced by the same weight portion of conventional nano-silicon dioxide.
[0090] Comparative Example 2
[0091] Based on Example 4, the only difference is that the modified nanofiller is replaced by the same weight portion of polypropylene.
[0092] Comparative Example 3
[0093] Based on Example 1, the only difference is that the modified nanofiller is replaced by the same weight portion of polypropylene.
[0094] The test samples prepared in the above embodiments and comparative examples were respectively subjected to wear resistance test, self-repairing performance test, tensile strength and elongation at break test.
[0095] Wear resistance test: Take the prepared sample and cut it into test pieces of the same size, with a diameter of 100 mm and a thickness of 2 mm. Use the TABER wear tester and load an appropriate grinding wheel (such as the CS-17 grinding wheel) with a load weight of 500 g. Set the number of wear cycles to 1000 times. Before and after the test, use an electronic balance to measure the mass loss of the sample to evaluate the wear resistance of the material.
[0096] Self-healing performance test: Take a sample and use a scratch tester to form a scratch of fixed depth and width (depth 0.1mm, width 0.5mm) on its surface. Observe the scratches and take photos to record the initial morphology of the scratches. Place the scratched sample on a hot plate, heat it to the activation temperature of the self-healing microcapsules (80°C), and keep heating for 2 hours. Take photos again to record the morphology of the scratches after repair. Use a 3D profilometer to measure the depth and width of the repaired scratches.
[0097] The test results are as follows:
[0098]
[0099]
[0100] Wear resistance (weight loss)
[0101] In Examples 1-3, with the increase of modified nanofillers, the wear resistance is significantly improved (weight loss is reduced from 12 mg to 8 mg), which shows that nanofillers have a significant effect on improving wear resistance.
[0102] In Examples 4-6, the materials with added microcapsules showed stable wear resistance, which was slightly inferior to that of Example 3 containing only modified nanofillers, but still significantly better than the comparative materials.
[0103] Comparative Examples 1-3 performed poorly, especially Comparative Example 3 (pure polypropylene), which had the worst abrasion resistance and a weight loss of up to 40 mg.
[0104] Self-repair performance (repair efficiency)
[0105] Examples 1-3 have basic self-repair capabilities derived from the reversible reaction of dynamic covalent bond precursors, but their repair efficiency is relatively low.
[0106] Examples 4-6 showed good self-healing properties, especially when the microcapsules were combined with the dynamic covalent bond precursor, a dual repair mechanism could be achieved, among which Example 6 had the highest repair efficiency, reaching 85%. This shows that the combination of PDX and PBAD mixed core material has the best self-healing performance.
[0107] Although Comparative Example 2 (containing only microcapsules) has certain self-repairing properties, the repair efficiency is low due to the lack of reinforcement of nanofillers.
[0108] Tensile strength and elongation at break
[0109] The tensile strength and elongation at break in Examples 1-3 were good, and the mechanical properties of the materials were improved with the increase of the nanofiller content.
[0110] Although the tensile strength of Examples 4-6 was slightly affected by the addition of microcapsules, it was maintained at a relatively high level overall.
[0111] The tensile strength and elongation at break of Comparative Examples 1-3 are significantly lower than those of the embodiments, especially Comparative Example 3 (pure polypropylene), which has the worst mechanical properties.
[0112] In summary, the modified nanofiller significantly improves the wear resistance of polypropylene, and when used in combination with self-healing microcapsules, the wear resistance remains at a high level. The embodiments containing self-healing microcapsules show excellent self-healing properties, especially Example 6, where the core material is a combination of PDX and PBAD, which performs best in terms of repair effect. The nanofiller performs well in improving tensile strength and elongation at break, while the introduction of microcapsules slightly affects the tensile strength, but still maintains good mechanical properties.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly wear-resistant fresh-keeping box cover, characterized in that: The raw materials of the highly wear-resistant fresh-keeping box cover include: polypropylene and modified nano filler, wherein the modified nano filler is a nano filler loaded with a dynamic covalent bond precursor, and the mass ratio of polypropylene to modified nano filler is 1:(0.01-0.05).
2. The highly wear-resistant fresh-keeping box cover according to claim 1, characterized in that: The dynamic covalent bond precursors are fumaric anhydride and cyclopentadiene.
3. The highly wear-resistant fresh-keeping box cover according to claim 1, characterized in that: The preparation method of the modified nanofiller comprises: adding the nanofiller into ethanol to prepare a suspension with a mass concentration of 1-5wt%, adding γ-glycidyloxypropyltrimethoxysilane of 1-2wt% of the mass of the nanofiller, ultrasonically stirring for 1-2h, then heating to 50-70°C, keeping warm and stirring for 2-4h, filtering and drying to obtain an activated filler, adding the activated filler into a fumaric anhydride solution, heating to 50-60°C, keeping warm and stirring for 2-3h, filtering and drying, then adding into a cyclopentadiene solution, heating to 30-50°C, keeping warm and stirring for 1-3h, filtering and drying to obtain the modified nanofiller.
4. The highly wear-resistant fresh-keeping box cover according to claim 3, characterized in that: The nano filler is nano silicon dioxide, and the average particle size thereof is 20-100 nm.
5. The highly wear-resistant fresh-keeping box cover according to claim 1, characterized in that: The raw materials also include self-repairing microcapsules, and the mass ratio of polypropylene to self-repairing microcapsules is 1:(0.01-0.05). The core material of the self-repairing microcapsules is at least one of dioxanone and polybutyrolactone diol, and the shell material is polyurethane.
6. The highly wear-resistant fresh-keeping box cover according to claim 5, characterized in that: The preparation method of the self-repairing microcapsule comprises: Prepare the aqueous phase: add 0.5-1 wt% polyvinyl alcohol to deionized water, heat to 55-65°C, stir to dissolve, and cool to obtain the aqueous phase; Preparation of oil phase: dissolving an appropriate amount of core material and isocyanate in dichloromethane to form an oil phase, wherein the mass concentration of the core material in the oil phase is 3-5wt%, and the amount of isocyanate is 1-5wt% of the core material; Emulsification: slowly add the oil phase to the water phase, stirring and emulsifying at 3000-5000 rpm, stirring for 20-30 minutes, the volume ratio of oil phase to water phase is 1: (4-10); Polymerization: Add polyisocyanate to the emulsified system and heat to 50-60°C. After the addition is complete, stir the mixture for 2-3 hours at this temperature, filter, wash and dry to obtain microcapsules.
7. The highly wear-resistant fresh-keeping box cover according to claim 6, characterized in that: The drying temperature is 50-60℃.
8. The highly wear-resistant fresh-keeping box cover according to claim 5, characterized in that: The core material is obtained by mixing dioxanone and polybutyrolactone diol in a mass ratio of 1:(2-3).
9. The method for preparing the highly wear-resistant fresh-keeping box cover according to any one of claims 1 to 8, characterized in that: The steps include: The raw materials are mixed and added into a twin-screw extruder for melt blending and extrusion, the extruded composite material particles are cooled and collected, and then injection molded by an injection molding machine to obtain a wear-resistant fresh-keeping box cover.
10. The method for preparing the highly wear-resistant fresh-keeping box cover according to claim 9, characterized in that: The temperature of the feeding zone of the extruder is 160-180°C, the temperature of the melting zone is 180-200°C, and the temperature of the discharging zone is 190-210°C.
Citation Information
Patent Citations
Self-healing siloxane elastomers
CA3000975A1
High-wear-resistance plastic floor and preparation method thereof
CN118061628A
Shape memory polymer aerogel composites
US20100144962A1
Cementitious compositions comprising fiber-supported pozzolanic materials
WO2024118514A1